O currículo escolar e a construção da cultura escrita na alfabetização: um estudo voltado para o 1° e 2° anos do ensino fundamental - Rodrigues, Francisca Lima (2008)
This study is part of the researching field of Curriculum, Teaching and School Practices of the Education Master s Degree course at Universidade Federal de Santa Maria and aims at comprehending the organization of the written language teaching in the 1st and 2nd grades of the Elementary School and its relationship between the construction of the written culture in literacy. In order to achieve the goals proposed and obtain an approach to the research problem we searched in the qualitative approach of research, more precisely in the multiple case study, for aids to the development of the investigation. For this, three public schools from Santa Maria-RS collaborated, one from the municipal teaching system and two state schools. The instruments used for data collection were the documents analysis, in this case the documents selected for the analysis were the school Political Pedagogical Project and the school syllabus. The interviews made, had the collaboration of nine teachers of the grades studied. From the content analysis two categories emerged: Construction of the curriculum for the lecto-writing teaching and Concretization of the curriculum for the lecto-writing teaching , that collaborated on/with a deeper comprehension of the thematic being studied. This way, we can say it is necessary changes in the configuration of the curriculums for the written language teaching and, consequently, in their concretization in order to make the quality of the mother tongue teaching possible in the sense to provide inclusion for the educatees in the written culture. In this way, we emphasize that these transformations will only be possible if there is a compromise among everyone involved with the school, once the necessity to change can be reached taking into account the reality existent, projecting the reality wished and, in this way, actions to achieve the new reality can be searched in collectively. Thus, we also highlight the importance of the teachers involved in the lecto-writing teaching and based on this, we emphasize the importance of the teachers continued formation as a possibility of enlarging and deepening the teachers production. We believe this formation can happen in the school, through actions that promote collective studies, in a way the teachers together can have contact with the productions about the different themes related to literacy and curriculum. So, that through the share of ideas they can discuss, reflect and comprehend to (trans)form and (trans)form themselves.